2001
DOI: 10.1103/physrevb.63.085111
|View full text |Cite
|
Sign up to set email alerts
|

Second-harmonic generation spectroscopy: A technique for selectively probing excitons

Abstract: We show that second-harmonic generation ͑SHG͒ and sum-frequency generation ͑SFG͒ are selective tools for probing excitons. In SHG and SFG measurements performed on C 60 and CuCl films we observe Frenkel and Wannier excitons, respectively. On the other hand, no second-harmonic ͑sum-frequency͒ intensity enhancement was observed at energies above the conductivity gap. This is in strong contrast to, for instance, one-photon and two-photon absorption experiments. The selectivity of SHG and SFG for excitons compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 38 publications
(66 reference statements)
1
9
0
Order By: Relevance
“…4͒, one sees peaks at 3.7 and 2.1 eV. The existence of a transition at 2.1 eV is consistent with nonlinear optical spectroscopy 12 and EELS. 13,17 The peak at 3.7 is more intense than the 2.1 eV peak.…”
Section: ͑2͒supporting
confidence: 81%
See 1 more Smart Citation
“…4͒, one sees peaks at 3.7 and 2.1 eV. The existence of a transition at 2.1 eV is consistent with nonlinear optical spectroscopy 12 and EELS. 13,17 The peak at 3.7 is more intense than the 2.1 eV peak.…”
Section: ͑2͒supporting
confidence: 81%
“…A way around this limitation is to use nonlinear optical techniques but the interpretation and implementation of these methods may not be straightforward or unambiguous. 12 In addition to optical techniques, the electronic structure of C 60 has been investigated using electron energy-loss spectroscopy ͑EELS͒. 13,14 This technique is not constrained by selection rules but possible limitations include multiple scattering and surface effects.…”
mentioning
confidence: 99%
“…In this way Sawatzky and coworkers [45,80] showed that the energy of the transition into the singlet exciton is resonant to photons with an energy of 1.826 eV (666 nm). Kern and coworkers [75] generated an exciton population by means of pulses with 3.49 eV photon energy (355 nm).…”
Section: Electronic States In C 60mentioning
confidence: 96%
“…28,29 . The concept of Wannier excitons was used in the SHG study of CuCl, whereas Frenkel excitons were explored in SHG studies of a C 60 molecular crystal 30,31 .…”
Section: Introductionmentioning
confidence: 99%